PENGARUH PENERAPAN MODEL PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI - Ekawaty, Defriana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThe influence of the application of the model of learning picture and picture on the skills of writing narrative essay of fourth grade students of elementary school of North 27 Pontianak. This study aims to determine the influence of narrative writing skills by using the picture and picture model of fourth grade students of elementary school of North 27 Pontianak The method used in this research is experimental method. Form of experimental research used is quasi exsperimental design with type One Group Pretest-Posttest. Population in this research is all of fourth grader of North 27 elementary school of North Pontianak 27 people Based on the analysis of data obtained from the pre-test obtained an average value of 49.5. While the average value of post-test result is 65,13. From result of t-test analysis obtained t count equal to 8,314 and t table = 2,479. This means 8.314> 1.706, then t arithmetic> t table, it can be said Ho rejected and Ha accepted. So it is concluded that there is influence of the use of model Picture and Picture to Writing Skill Writer Narasi Student Class IV State Elementary School 27 Pontianak Utara.Â Keywords: Influence, picture and picture model, writing skill, narrative essay